2011
DOI: 10.1289/ehp.1002883
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bisphenol A and Triclosan on Immune Parameters in the U.S. Population, NHANES 2003–2006

Abstract: BackgroundExposure to environmental toxicants is associated with numerous disease outcomes, many of which involve underlying immune and inflammatory dysfunction.ObjectivesTo address the gap between environmental exposures and immune dysfunction, we investigated the association of two endocrine-disrupting compounds (EDCs) with markers of immune function.MethodsUsing data from the 2003–2006 National Health and Nutrition Examination Survey, we compared urinary bisphenol A (BPA) and triclosan levels with serum cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(159 citation statements)
references
References 42 publications
2
151
1
5
Order By: Relevance
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…For example, 14 US studies used data from the National Health and Nutrition Examination Survey (NHANES) (Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al Tier 1: Design: clinical trials/ Exposure: assessment based on a sufficient number of samples per individual to estimate exposure over the appropriate duration, or through the use of adequate long-term sampling; for chemicals for which one sample may be sufficient to fully characterize exposure, inclusion of evidence that errors can be considered sufficiently small; randomized experimental studies with inclusion of increased TCS levels following intervention/ Data analysis: randomization or demonstrated comprehensive evaluation of control variables and included sensitivity analyses. Tier 2: Design: cohort studies and case-control studies with incident cases; studies with both cohort and crosssectional designs/ Exposure: > one sample but without explicit evaluation of error or had > one TCS measure but used each measure as a separate observation; other experimental studies/ Data analysis: applied appropriate statistical methods but did not include sensitivity analyses.…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Investigators have noted that triclosan and parabens have endocrine disrupting properties and possibly immune modulating properties. 13,[15][16][17] Three recent studies of triclosan and parabens established an association of exposure with allergy or hay fever diagnosis. 16 -18 The mechanism for this association remains unclear, and none of these studies evaluated the relationship in the context of the atopic march/eczema history.…”
mentioning
confidence: 99%
“…Two other studies in the US [16] and China [17] reported an association between BPA exposure and coronary disease at the time of diagnosis and obesity and insulin resistance, respectively. In addition, a study found associations between urine BPA and immune function and allergy [18]. These cross-sectional analyses have the same weaknesses that limit their interpretation.…”
Section: Bisphenol a And Human Healthmentioning
confidence: 99%